2019
DOI: 10.1016/j.scienta.2019.108787
|View full text |Cite
|
Sign up to set email alerts
|

The role of ethylene and 1-MCP in early-season sweet cherry ‘Burlat’ storage life

Abstract: Sweet cherries (Prunus avium L.) are highly appreciated because of their bioactive compound content and attractive organoleptic characteristics; however, they are very perishable. The aim of this work was to investigate whether ethylene and its antagonist 1-MCP affect the postharvest quality of an early-season sweet cherry cultivar, allowing storage life extension. 'Burlat' sweet cherries were subjected to three treatments at 1°C for one month: i) control (air); ii) continuous ethylene supplementation (10 µL L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Nevertheless, DI and BI of samples treated with ethylene prior to 1-MCP was still observably lower than that of control, especially in later stage of shelf life. Analogously, Serradilla et al (2019) reported that 1-MCP showed a positive impact on DI in early-season sweet cherries "Burlat" that was similar with our previous results on kiwifruits and blueberries (Xu et al, 2020). Furthermore, both Wu et al (2016) and Chen et al (2016) reported a decrease in BI of 1-MCP-treated pears in comparison with the untreated samples.…”
Section: Effect Of Different Treatments On DI and Bisupporting
confidence: 87%
“…Nevertheless, DI and BI of samples treated with ethylene prior to 1-MCP was still observably lower than that of control, especially in later stage of shelf life. Analogously, Serradilla et al (2019) reported that 1-MCP showed a positive impact on DI in early-season sweet cherries "Burlat" that was similar with our previous results on kiwifruits and blueberries (Xu et al, 2020). Furthermore, both Wu et al (2016) and Chen et al (2016) reported a decrease in BI of 1-MCP-treated pears in comparison with the untreated samples.…”
Section: Effect Of Different Treatments On DI and Bisupporting
confidence: 87%
“…Weight loss was measured at each sampling point, compared with an initial weight of 250 g of sweet cherries ( n = 3), and calculated in percentage [ 26 ]. Stem browning and non-commercial fruit were measured by visual inspection by qualified staff, as reported by Candan et al [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Change in the expression of ABA degradation related gene FveCYP707A4a influenced the expression of FveCEL2, FvePL, and FvePG, indicating that ABA is involved in the fruit softening of strawberry [30]. Ethylene, as the critical facilitator of climacteric fruit ripening, has also been reported in promote fruit softening in non-climacteric fruit sweet cherry [31], conversely, pre-harvest methyl jasmonate (MeJA) treatments could significantly inhibited the fruit softening of sweet cherry [32], but the specific molecular mechanism is not clear.…”
Section: Introductionmentioning
confidence: 96%